2012
DOI: 10.1002/pmic.201200043
|View full text |Cite
|
Sign up to set email alerts
|

Myosin light chain isoforms retain their species‐specific electrophoretic mobility after processing, which enables differentiation between six species: 2DE analysis of minced meat and meat products made from beef, pork and poultry

Abstract: Investigation of protein changes as well as authentication of meat is particularly difficult in processed meat products due to their different composition, complexity and very often inhomogeneity. The aim of this study was to check if the inter-species differences in the expression of myosin light chain (MLC) isoforms observed in raw meat were retained in meat products. MLCs from mixtures of minced meat (16 variants), frankfurters and sausages (15 products) made from cattle, pig, chicken, turkey, duck and goos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 34 publications
1
34
0
2
Order By: Relevance
“…On the same context, Pospiech (2011b and2012b) observed the inter-species differences in myosin light chain isoforms (MLC) in the raw and processed meat and meat products of some animal species including some poultry species (chicken, turkey, duck and goose) in addition to pig and cattle depending on the species-specific electrophoretic mobility. Zhao et al (2014) reported that mid-infrared ATR spectroscopy could help in identifying the authentic higher and lower quality beef burger samples from other samples adultrated by beef offal under fresh and freezing conditions.…”
Section: The Role Of Proteomic Technology and Peptide Biomarkers In Imentioning
confidence: 99%
“…On the same context, Pospiech (2011b and2012b) observed the inter-species differences in myosin light chain isoforms (MLC) in the raw and processed meat and meat products of some animal species including some poultry species (chicken, turkey, duck and goose) in addition to pig and cattle depending on the species-specific electrophoretic mobility. Zhao et al (2014) reported that mid-infrared ATR spectroscopy could help in identifying the authentic higher and lower quality beef burger samples from other samples adultrated by beef offal under fresh and freezing conditions.…”
Section: The Role Of Proteomic Technology and Peptide Biomarkers In Imentioning
confidence: 99%
“…Были установлены межвидовые различия в 2DGE профиле белков между свиньями, курами, КРС, индю-ками, утками и гусями как в сырье, так и в перерабо-танных мясопродуктах, таких как ферментированные колбасы [21,22].…”
Section: Proteomics In Research On Meat Fraudunclassified
“…Inter-species differences in 2DGE protein profile was detected between pig, chicken, cattle, turkey, duck and goose in both raw material and processed meat products such as fermented sausage [21,22].…”
Section: протеомика в исследовании благополучия животныхmentioning
confidence: 99%
“…Compared to SDS-PAGE, IEF generally presents better band resolution, but gives more complicated and less consistent patterns, which also advises against its use for the authentication of processed meat products. Better results can be achieved by means of 2-DE coupled to image analysis software since it allows the separation of thousands of proteins in one gel and analysis of changes in protein expression levels, such as isoforms and posttranslational modifications (Montowska and Pospiech, 2012b). Species-specific differences in the molecular weight and isoelectric point of skeletal muscle myosin light chain (MLC) isoforms of six species, namely, cow, pork, chicken, turkey, duck, and goose, were revealed by 2-DE (Montowska and Pospiech, 2011b).…”
Section: Electrophoretic Techniquesmentioning
confidence: 99%
“…The authors concluded that each species showed a characteristic pattern on 2-DE gels that can be used for species identification in raw meat mixtures since even a 2% difference in the sequences of MLC resulted in different electrophoretic mobilities. Later, the same methodology was applied to investigate if the interspecies differences noticed in the expression of MLC isoforms in raw meat were also observed in minced meat and meat products (frankfurters and sausages) produced from the same six species (Montowska et al, 2012b). The results showed that the MLC suffered only a relatively small degradation after processing, enabling species identification in all samples when the combination of all the three MLC isoforms was taken into account, and as long as the content of meat of one species in the mixture was not lower than 10%.…”
Section: Electrophoretic Techniquesmentioning
confidence: 99%